Metric-scalar gravity with torsion and the measurability of the non-minimal coupling - Accioly, A. [UNESP]; Blas, H. (World Scientific Publ Co Pte Ltd, 2007)
The measurability of the non-minimal coupling is discussed by considering the correction to the Newtonian static potential in the semiclassical approach. The coefficient of the gravitational Darwin term (GDT) gets redefined by the non-minimal torsion scalar couplings. Based on a similar analysis of the GDT in the effective field theory approach to non-minimal scalar, we conclude that for reasonable values of the couplings the correction is very small.
Keywords: Foldy-Wouthuysen transformation; non-minimal coupling; torsion; metricscalar gravity